GENE INTERACTIONS OF ALPHA-ADDUCIN AND LANOSTEROL SYNTHASE IMPACT RENAL IMPAIRMENT IN SALT SENSITIVE HYPERTENSION. (June 2018) - Maggioni, C.; Lanzani, C.; Zagato, L.; Messaggio, E.; Citterio, L.; Simonini, M.; Brioni, E.; Carpini, S. Delli; Magnaghi, C.; Hamlyn, J.M.; Manunta, P.; Vespa, M.
Abstract : Objective: The genes involved in the development of renal damage and salt sensitive hypertension (SS) are unknown. Renal impairment is considered to be the major determinant of salt sensitive hypertension. Design and method: We explored the roles of alpha-adducin (ADD1) and lanosterol synthase (LSS), genes coding for structural proteins of the cell membrane and Endogenous Ouabain (EO), respectively, on renal Na handling and their genetic interactions in a large cohort of naïve hypertensive patients (NHP) whose salt sensitive phenotype was characterized. Acute saline load (NaCl 308 mEq/2 h e.v.) was performed in 774 NHP (age 44.95 ± 9.61 years), and functional and hormone renal parameters were tested. Results: Under baseline conditions NHP carriers of the LSS AA genotype showed lower GFR (n = 68, 115.7 ± 4.6 ml/min) compared to LSS C carriers (124.6 ± 1.4 ml/min, p = 0.066). After an acute saline test, GFR increased in both groups, while the urinary volume and urinary creatinine were lower in LSS AA. Analysis of gene*gene interactions demonstrated that NHPs carrying both mutated GT ADD1 and homozygous for LSS C variants excreted the sodium load more rapidly than their ADD1*LSS mutated variants. On the other hand, an additive (p = 0.003) effect of ADD1 GT & LSS AA variants on the pressure-natriuresis relationship was observed, with a significant right shift along the x axis. Finally, circulating EO was modified according to the LSS variant: in SS LSS AA, EO rose signicantly during the recovery while in SR LSS AA, EO was suppressed as were aldosterone and PRA. Conclusions: The results demonstrate: 1. NHPs carrying the LSS AA genotype have reduced GFR under basal conditions; 2. Salt Sensitive LSS AA are EO non-modulators, since their circulating EO does not decline under circumstances where the RAAS is suppressed; 3. The ADD1*LSS interaction identifies those NHPs with impaired renal Na handling.